Potensi karbon stok dan valuasi nilai ekonomi karbon stok pada tegakan eboni - Mario Damanik; Khaerul Amru (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
One of the important activities to achieve the implementation of REDD+ activities is the measurement and reporting of carbon stocks (Masripatin et.al. 2010). Information on the potential for carbon stocks in a plant stand or forest area can provide an overview for related parties of the potential carbon stocks and the added value that will be obtained if it maintains and develops a certain plant species to support the reduction of greenhouse gas emissions. This study aims to determine the potential of biomass, carbon stocks, and economic valuation of the carbon stocks potential of several Ebony stands contained in the Kawanua Arboretum BP2LHK Manado. The types of Ebony stands that were the object of this study were Dyospiros celebica, Dyospiros rumphii, and Dyospiros ebenum. Determination of biomass potential and carbon stocks using the allometric equation. The economic valuations of each potential carbon stocks of Ebony stands are obtained based on the selling value of carbon set by the World Bank Group. Based on the results of the study, it is known that the carbon stocks potential of each Ebony stand, namely Diospyros rumphii, is 74.246 tons/ha, followed by the potential carbon storage in the Diospyros celebica stand of 67.768 tons/ha and Diospyros ebenum of 64.977 tons / ha, while the economic valuation value of the highest carbon storage potential is found in the Diospyros rumphii stand of USD 148.492 followed by Diospyros celebica is USD 135.536 and Diospyros ebenum is USD 129.954